An 8/15‐channel Tx/Rx head neck RF coil combination with region‐specific B1+ shimming for whole‐brain MRI focused on the cerebellum at 7T. Issue 3 (9th February 2018) - Pfaffenrot, Viktor; Brunheim, Sascha; Rietsch, Stefan H. G.; Koopmans, Peter J.; Ernst, Thomas M.; Kraff, Oliver; Orzada, Stephan; Quick, Harald H.
Abstract : Purpose: To design and evaluate an 8/15‐channel transmit/receive (Tx/Rx) head‐neck RF coil combination with region‐specific B 1 + shimming for whole‐brain MRI with focus on improved functional MRI of the cerebellum at 7 T. Methods: An 8‐channel transceiver RF head coil was combined with a 7‐channel receive‐only array. The noise parameters and acceleration capabilities of this 8Tx/15Rx coil setup were compared with a commercially available 1Tx/32Rx RF head coil. Region‐specific 8‐channel B 1 + shimming was applied when using the 8Tx/15Rx RF coil. To evaluate the capability for functional MRI of the cerebellum, temporal SNR and statistical nonparametric maps for finger‐tapping experiments with 14 healthy subjects were derived by applying a variable slice thickness gradient‐echo echo‐planar functional MRI sequence. Results: The 8Tx/15Rx setup had a lower maximum noise correlation between channels, but higher average correlations compared with the 1Tx/32Rx coil. Both RF coils exhibited identical g‐factors in the cerebellum with R = 3 acceleration. The enlarged FOV of the 8Tx/15Rx coil in combination with region‐specific B 1 + shimming increased homogeneity of the transmission field and temporal SNR in caudal cerebellar regions. Temporal SNR losses in cranial parts were reduced, resulting in more highly significant voxels in the caudally activated areas and identical patterns in the cranial cerebellar parts during a finger‐tapping task. Conclusion: Compared with the 1Tx/32Rx RF coil, the presented 8Tx/15Rx RF coil combination successfully improves functional MRI of the human cerebellum at 7 T while maintaining whole‐brain coverage. A clear temporal SNR gain in caudal cerebellar regions is shown.